KANTOR DINAS LINGKUNGAN HIDUP KOTA GORONTALO - Zamaludin Mantali; Sri Sutarni Arifin; Muhammad Rijal Syukri (JAMBURA Journal of Architecture, 2021)
ABSTRACT. Environmental Service Office Gorontalo City which is located on Jl. Rajawali Ex. South Heledulaa Kec. East City Gorontalo City, has tasks in the field of management and environmental protection of the City of Gorontalo, which still lacks building facilities or space to run all government needs. For this reason, the Gorontalo City Environmental Office Office needs to have a separate building so that it can accommodate all official activities carried out in government affairs, in this case, it is necessary to have a building or room for each sector and facilities Others, such as the Impact Analysis Laboratory Environment, nursery, DAM Trucks, totaling 20 units and motorbike carts totaling 40 units, Equipment Warehouse, Parks, Halls or meeting rooms, prayer rooms, TPS 3R, Banks trash, waiting room, and others. Because looking at the condition of the Gorontalo City Environmental Service office, whose current building feasibility does not meet the requirements of the actual office function.  Keywords: office, environment, Gorontalo, tropical ABSTRAK. Kantor Dinas Lingkungan Hidup ‎Kota Gorontalo yang terletak di Jl. ‎Rajawali Kel. Heledulaa Selatan ‎Kec. ‎Kota Timur Kota Gorontalo, mempunyai ‎tugas di bidang pengeloloan dan ‎perlindungan ‎lingkungan hidup Kota ‎Gorontalo, yang masih kekurangan ‎fasilitas gedung atau ruangan untuk ‎‎menjalankan semua kebutuhan ‎kepemerintahan. Untuk itu Kantor Dinas ‎Lingkungan Hidup Kota ‎Gorontalo perlu ‎ada satu bangunan tersendiri agar bisa ‎mewadahi semua aktifivitas kedinasan ‎yang ‎dilakukan dalam urusan ‎kepemerintahan, dalam hal ini perlu ‎adanya gedung atau ruangan  untuk ‎‎masing-masing bidang serta fasilitas ‎lainya seperti Laboratorium Analisis ‎Dampak ‎Lingkungan,tempat pembibitan, ‎tempat mobil DAM Truk berjumlah 20 ‎unit dan Gerobak motor ‎berjumlah 40 ‎unit , Gudang Peralatan, Taman, Aula ‎atau Ruang rapat,mushola,TPS 3R, ‎Bank ‎sampah, ruang Tunggu dan Lain-‎lain. Karena melihat kondisi kantor ‎dinas lingkungan hidup kota ‎gorontalo  ‎yang kelayakan bangunanya saat ini ‎tidak memenuhi syarat sebagaimana ‎fungsi kantor ‎yang sebenarnya.‎ Kata kunci: kantor, lingkungan hidup, Gorontalo, tropis